The prognostic impact of depression or depressive symptoms on patients with head and neck cancer: A systematic review and meta‐analysis. Issue 11 (15th September 2021) - Van der Elst, Sarah; Bardash, Yonatan; Wotman, Michael; Kraus, Dennis; Tham, Tristan
Abstract: Background: This systematic review and meta‐analysis sought to assess the extent to which pretreatment depression or depressive symptoms are related to prognosis in patients with head and neck cancer (HNC). Methods: Medline, EMbase, Scopus, and The Cochrane Library databases were searched. A meta‐analysis was done to generate a forest plot and pooled hazard ratio (HR) with 95% CI for overall survival (OS). RevMan 5.3 and Meta Essentials were used for statistical analysis. Results: Based on seven studies involving 1743 patients, the results showed that HNC patients with pretreatment depression or depressive symptoms had worse OS than patients without depression or depressive symptoms, with an HR of 1.33, 95% CI 1.16–1.52, p = <0.0001. There is heterogeneity in the pooled summary effect ( I 2 = 80%, p < 0.0001). Conclusions: Pretreatment depression or depressive symptoms may indicate worse OS in patients with HNC. The pooled analysis demonstrated a statistically significant effect. These results were limited by mild heterogeneity.